REVITALISASI PERMAINAN DAM-DAMAN PADA TAMAN KOTA DENGAN UNSUR SEJARAH KONFLIK ANTARA KESULTANAN CIREBON DAN KERAJAAN SUMEDANG LARANG - Muminah, Afifah; A. S. , Vania Dwi; Rosalina, Asri; Fajarriny, Erri; Nadia (Jurnal Kreatif : Desain Produk Industri dan Arsitektur, 2025)
Children love to play, but with the rapid development of information technology there has been a change in the way children play. From playing directly and socializing with friends, to playing through gadgets. This makes children gradually lose their skills in socializing and playing with their friends. Dam-daman is a traditional game that has begun to be less known in the community. Researchers revitalized the game of checkers as a form of play that motivates children to play outside and socialize. The research was conducted by implementing the ATUMICS method. The transformation of the checkers game tradition is carried out by identifying using the ATUMICS table. Thus, the design of checkers games in public spaces is produced that allows children to interact and can motivate other visitors to public spaces, not only children. Thus, the dam-daman game can be preserved and also the content about its history is known by the public.